Serum undercarboxylated osteocalcin levels are related to bone disease in hemodialysis and peritoneal dialysis patients - Alpdemir, Medine; Fidancı, Vildan; Alpdemir, Mehmet Fatih; Azak, Alper; Saydam, Gülsevim; Duranay, Murat; Yücel, Doğan (The European Research Journal, 2021)
Objectives: In our study, we investigated whether the undercarboxylated osteocalcin (ucOC) is an indicator of bone turnover for patients treated with hemodialysis (HD) or peritoneal dialysis (PD). Furthermore, we have examined the relationships between ucOC levels and other bone inidicators such as osteocalcin (OC), bone specific alkaline phosphatase (B-ALP), calcitonin, vitamin D, intact parathyroid hormone (iPTH), calcium (Ca), phosphate (P), magnesium (Mg) and bone mineral density (BMD). Methods: Study group was consisted of 24 HD, 30 PD patients and 30 control subjects. ucOC measurements were based on precipitation of carboxylated OC with barium sulfate. After precipitation, ucOC was measured in supernatant by ELISA. Results: In chronic kidney disease (CKD), increased ucOC levels were present both in HD and PD groups. The ucOC levels in HD group were higher than those of PD group. ucOC levels in samples after HD were lower than in samples before HD. But there is no difference between groups for ucOC% levels. We observed that ucOC levels for CRF were higher compared to that of control group and statistically significant. ucOC levels were positively correlated with OC, B-ALP, ALP, iPTH, P and Mg levels. There were negative and significant correlations between ucOC levels and BMD values. ucOC has a good discrimination power for both high and low turnover ROD groups. Conclusions: ucOC is a useful marker to evaluation of bone metabolism in patients undergone hemodialysis or peritoneal dialysis in end-stage renal disease.